1997
DOI: 10.1016/s0005-2728(96)00174-0
|View full text |Cite
|
Sign up to set email alerts
|

Lack of copper insertion into unprocessed cytoplasmic nitrous oxide reductase generated by an R20D substitution in the arginine consensus motif of the signal peptide

Abstract: Metal insertion into an engineered cytoplasmic form of the multicopper enzyme N2O reductase (N2OR) (EC 1.7.99.6) of Pseudomonas stutzeri was studied. The reductase has an unusually long presequence of 50 amino acids for translocation into the periplasm. The signal peptide of N2OR shares a conserved twin-arginine sequence motif with the signal peptides of other N2O reductases and a sizeable group of periplasmic or membrane-bound enzymes, requiring cofactor insertion or processing. A catalytically inactive reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 10 publications
2
42
1
Order By: Relevance
“…A similar result was achieved by reconstitution of purified nitrous oxide reductase from which the copper centers had been chemically removed (8). In contrast, the characteristic electronic spectrum of Cu A could be obtained when a translocationincompetent mutant of nitrous oxide reductase in which the twin-arginine motif was mutated (R20D) was reconstituted with copper, but the insertion process was slow and resulted in a weak retention of copper (11). These data led to the suggestion that the twin-arginine motif of NosZ may confer both translocational competence and delivery to a specific system involved with copper insertion.…”
Section: Discussionmentioning
confidence: 73%
“…A similar result was achieved by reconstitution of purified nitrous oxide reductase from which the copper centers had been chemically removed (8). In contrast, the characteristic electronic spectrum of Cu A could be obtained when a translocationincompetent mutant of nitrous oxide reductase in which the twin-arginine motif was mutated (R20D) was reconstituted with copper, but the insertion process was slow and resulted in a weak retention of copper (11). These data led to the suggestion that the twin-arginine motif of NosZ may confer both translocational competence and delivery to a specific system involved with copper insertion.…”
Section: Discussionmentioning
confidence: 73%
“…that the mislocalization of NosZ in TF140 impairs its physiological function. Indeed, mutational analysis of the NosZ system from Pseudomonas stutzeri has shown that the export to the periplasm is a prerequisite of the protein to be physiologically active (11). Due to the lack of an appropriate NosZ antibody, it was not possible to investigate the cellular localization of the enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…The primary structures of NosZ from various bacteria, including R. eutropha, are highly conserved and are all characterized by an unusually long N-terminal twin-arginine signal peptide of 45 to 56 aa (11,47).…”
mentioning
confidence: 99%
“…Some examples of Tat targeting signals are shown in Fig. 2. A number of site-directed mutagenesis experiments using natural substrates of the Tat pathway have confirmed that the consecutive arginine residues of the consensus motif play a key role in the export process (Dreusch et al, 1997;Gross et al, 1999;Halbig et al, 1999). However, there is growing evidence that Tat translocation does not always require the presence of an arginine pair.…”
Section: The Tat Signal Peptidementioning
confidence: 99%